Can nurses improve self-management among pediatric patients? A systematic review and meta-analysis. (13th November 2019) - Mele, A; Nardi, A; Prencipe, G P; Migliara, G; Massimi, A; Rega, M L; Anderson, G; Casasanta, D; De Vito, C; Damiani, G
Abstract: Background: Few studies report educational interventions for pediatric patients with asthma or diabetes type 1 as a fundamental instrument to engage them and improve their health. The aim of this systematic review and meta-analysis was to synthesize evidence about behavioral changes in life style, disease management and clinical outcome in pediatric patients after a structured educational intervention delivered by nurses. Methods: A systematic review of the literature was carried out in MEDLINE, Scopus and CINHAL including only RCTs. Methodological quality of the studies was assessed using Cochrane tool. Meta-analyses on HbA1c reduction for diabetes and hospitalization, emergency department (ED) visits and medication for asthma were carried-out. Results: Of the 3559 papers initially retrieved, 5 regarding diabetes and 19 asthma met the inclusion criteria for the systematic review and 14 for the meta-analyses. Included studies were highly heterogeneous in terms of type of intervention and follow-up duration. Almost all the studies showed an improvement but only few were statistically significant. All studies regarding diabetes showed a low risk of bias (only one RCTs had a high risk of bias in one domain), while almost all RCTs on asthma showed a high risk of bias. The pooled mean differences in favor of the experimental groups were: HBA1c -0.02 (IC95%: -0.26 - 0.22), Hospitalization 0.58 (IC95%: 0.19 - 1.78), Medication -0.10 (IC95%: -0.43 - 0.23), ED Visits 0.82 (IC95%: 0.44 - 1.54). Conclusions: There is a general agreement about the central role of educational intervention delivered by nurses to pediatric patients and the assessment of the behavioral changes after educational interventions is strongly recommended in pediatric population. However, more efforts are requested in designing studies on patients with asthma and to program more appropriate follow-up and periodic recall in order to engage pediatric patients in the management of their own chronic disease. Key messages: educational intervention delivered by nurses to pediatric patients with asthma or diabetes type 1 as a fundamental instrument to engage them. more efforts are requested in designing studies on patients with asthma and to program more appropriate follow-up and periodic recall in order to engage pediatric patients.